FT-IR spectroscopic investigations of surface and intercalated 2-aminopyrimidine adsorbed on sepiolite and montmorillonite from Anatolia - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 2003)
The adsorption of 2-amino pyrimidine (2APM) on sepiolite and montmorillonite has been investigated using FT-IR spectrometry. The intercalation of 2-amino pyrimidine within montmorillonite has been shown by X-ray diffraction to increase the interlayer spacings. 2APM interacted with montmorillonite by direct or indirect coordination (through water molecules) to the exchangeable cations. Adsorption on sepiolite was due to hydrogen bonding with surface Si–OH groups. It is concluded that endocyclic nitrogen is mainly involved in coordination. Moreover, amino group hydrogens may be involved in hydrogen bonding interaction with water molecules (NH…OH2).
Keywords: IR spectroscopy; Clay minerals; Montmorillonite; Sepiolite; Intercalation; Adsorption; Pyrimidine; Diazines